Accrued reductions in heart rate following transcutaneous vagal nerve stimulation in adults with posttraumatic stress disorder - Sundararaj, Srirakshaa; Gazi, Asim H.; Vaccarino, Viola; Shah, Amit J.; Inan, Omer T.; Bremner, J. Douglas (Frontiers in Neuroscience, 2025)
BackgroundPost-Traumatic Stress Disorder (PTSD) is a condition marked by chronic autonomic dysregulation, including heightened arousal and increased heart rate, contributing to a higher risk of cardiovascular disease (CVD). tcVNS has been shown in prior work to decrease arousal and reduce heart rate in participants with PTSD during stimulation and 2–3 min afterward. No studies have investigated effects of tcVNS on objective physiological markers such as heart rate over hour-long timescales.ObjectiveThe purpose of this study was to investigate the effects of active versus sham tcVNS on heart rate responses to stress in traumatized individuals with and without PTSD undergoing a 3 h traumatic stress reminder protocol. Understanding the effects of tcVNS on heart rate over extended periods lasting several hours is crucial to better assess its potential cardiovascular benefits and inform treatment strategies for this population.MethodsA total of 41 participants, including 22 with PTSD (sex: 16 female, six male; age: 41.5 ± 12.89 years) and 19 without (sex: nine female, 10 male; age: 32.79 ± 7.10 years), participated in a mechanistic clinical trial that elicited trauma-incited stress responses by replaying recorded traumatic scripts followed by active or sham tcVNS (double-blind, randomized). Continuous electrocardiogram data were collected and used to measure heart rate and temporal alignment and resampling of the beat-by-beat heart rate time series were performed to distinctively enable timepoint by timepoint averaging for the entire 3 h research visit. We then aggregated the responses across participants of the same group (active/sham × PTSD/non-PTSD) and investigated the effects of tcVNS on heart rate over the multi-hour protocol.ResultsAnalysis revealed accrued reductions in heart rate among participants with PTSD who received active tcVNS compared to those who received sham stimulation (P < 0.05). These effects were not observed in non-PTSD participants. Notably, heart rate reduced approximately 5% below baseline levels for participants with PTSD who received active tcVNS by the end of the ∼3 h-long protocol, indicating accrued effects of tcVNS on cardiac autonomic function.ConclusiontcVNS induces accrued reductions in heart rate for participants with PTSD, potentially suggesting a temporary reduction of chronic cardiac arousal associated with PTSD.